2011
DOI: 10.1007/s10096-011-1417-5
|View full text |Cite
|
Sign up to set email alerts
|

Is Escherichia coli urinary tract infection a zoonosis? Proof of direct link with production animals and meat

Abstract: Recently, it has been suggested that the Escherichia coli causing urinary tract infection (UTI) may come from meat and animals. The purpose was to investigate if a clonal link existed between E. coli from animals, meat and UTI patients. Twenty-two geographically and temporally matched B2 E. coli from UTI patients, community-dwelling humans, broiler chicken meat, pork, and broiler chicken, previously identified to exhibit eight virulence genotypes by microarray-detection of approximately 300 genes, were investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 36 publications
1
44
0
5
Order By: Relevance
“…coli is the major causative agent of UTIs in humans and domestic animals [38]. Recent studies suggest that animaloriginating E. coli has zoonotic potential for human infections [10,34]. Therefore, we investigated not only the characteristics of 10 E. coli isolates from dogs with cystitis but also the interaction between the canine UPEC isolates and human bladder epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…coli is the major causative agent of UTIs in humans and domestic animals [38]. Recent studies suggest that animaloriginating E. coli has zoonotic potential for human infections [10,34]. Therefore, we investigated not only the characteristics of 10 E. coli isolates from dogs with cystitis but also the interaction between the canine UPEC isolates and human bladder epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study on the relationships between human and canine E. coli isolates suggested that these isolates exhibit host specificity with respect to virulence factors [15]. However, several studies have recently shown that E. coli might have zoonotic potential, due to the considerable commonality observed between human and animal E. coli isolates from UTIs [10,12].…”
mentioning
confidence: 99%
“…The procedure was performed as previously described by Jakobsen et al (32). Briefly, mouse bladders were emptied prior to transurethral inoculation with 50 l of bacterial suspension (10 9 CFU/ml).…”
Section: Methodsmentioning
confidence: 99%
“…ExPEC virulence genes are common among E. coli isolates from food products, particularly raw meats (5) and especially poultry meat (7). However, although poultry-source E. coli isolates have been shown to cause UTI, sepsis, and meningitis in rodent models that mimic human ExPEC infections (8), the human health risk posed by poultry products is still a matter of some debate, since direct transmission of ExPEC from poultry to humans is difficult to document (4).…”
mentioning
confidence: 99%